Assessing the Consistency of the Design of Iranian Websites with Cultural Characteristics of their Target Users: An Investigation of the Hofstede Model - Mousavi, Maryamossadat (Information Management and Business Review, 2012)
The influence of culture on the design of websites has been researched extensively. A group of researchers has implemented Hofstede’s Cultural Dimensions as a proper framework to study this subject. The literature supports that cultural characteristics of the Hofstede model are significantly present in the design of websites. It also suggests that making a website compatible with the cultural characteristics of the target users facilitates effective interaction of the users with the websites. Building upon these observations, the present study has investigated the impact of Iranian culture on the design of Iranian university websites. We have measured the consistency of their design with the cultural characteristics of their target users and studied the possible improvements brought about by a culturally harmonious design. To this end, one sample t-test method is applied to compare the scores given by the end users for each cultural dimension, with the scores of the Hofstede model to measure the level of consistency. The results suggest that the design of Iranian university websites represents a more collectivistic and masculine culture with higher indices of power distance than what is specified in the Hofstede model and a change towards a more individualistic, elegant and informal design is necessary for the websites to improve their conformance to the cultural elements of Iranian users and improve their experience. To our knowledge, the present paper is novel in two aspects: firstly, it focuses on the case for Iran, which has not been extensively studied before; secondly, it makes a parallel study to measure the users’ preferences and compares it to the predictions made by the Hofstede model.